2023
DOI: 10.1038/s41598-023-28019-y
|View full text |Cite
|
Sign up to set email alerts
|

Salivary Huntingtin protein is uniquely associated with clinical features of Huntington’s disease

Abstract: Measuring Huntingtin (HTT) protein in peripheral cells represents an essential step in biomarker discovery for Huntington’s Disease (HD), however to date, investigations into the salivary expression of HTT has been lacking. In the current study, we quantified total HTT (tHTT) and mutant HTT (mHTT) protein in matched blood and saliva samples using single molecule counting (SMC) immunoassays: 2B7-D7F7 (tHTT) and 2B7-MW1 (mHTT). Matched samples, and clinical data, were collected from 95 subjects: n = 19 manifest … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 47 publications
0
2
0
Order By: Relevance
“…Prior research has primarily focused on CSF and blood, with only a limited number of publications reporting mHTT levels in saliva. 11,17,25 However, in these three body fluids, mHTT was difficult to detect in premanifest HDGECs and was undetectable in HCs. Our results showed that mHTT was detectable in tear fluid in all subjects (100%), including all premanifest HDGECs and all HCs.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Prior research has primarily focused on CSF and blood, with only a limited number of publications reporting mHTT levels in saliva. 11,17,25 However, in these three body fluids, mHTT was difficult to detect in premanifest HDGECs and was undetectable in HCs. Our results showed that mHTT was detectable in tear fluid in all subjects (100%), including all premanifest HDGECs and all HCs.…”
Section: Discussionmentioning
confidence: 90%
“…Recently, saliva was reported to be a successful source for quan-tifying mHTT comparable to plasma mHTT. 17 Here, we report the results of the first study on HD biomarkers in the tear fluid of premanifest and manifest HDGECs compared to healthy controls (HCs).…”
Section: Introductionmentioning
confidence: 99%